Diurnal tidal currents attributed to free baroclinic coastal-trapped waves on the Pacific shelf off the southeastern coast of Hokkaido, Japan. (15th April 2018) - Kuroda, Hiroshi; Kusaka, Akira; Isoda, Yutaka; Honda, Satoshi; Ito, Sayaka; Onitsuka, Toshihiro
Abstract: To understand the properties of tides and tidal currents on the Pacific shelf off the southeastern coast of Hokkaido, Japan, we analyzed time series of 9 current meters that were moored on the shelf for 1 month to 2 years. Diurnal tidal currents such as the K1 and O1 constituents were more dominant than semi-diurnal ones by an order of magnitude. The diurnal tidal currents clearly propagated westward along the coast with a typical phase velocity of 2 m s –1 and wavelength of 200 km. Moreover, the shape and phase of the diurnal currents measured by a bottom-mounted ADCP were vertically homogeneous, except in the vicinity of the bottom boundary layer. These features were very consistent with theoretically estimated properties of free baroclinic coastal-trapped waves of the first mode. An annual (semi-annual) variation was apparent for the phase (amplitude) of the O1 tidal current, which was correlated with density stratification (intensity of an along-shelf current called the Coastal Oyashio). These possible causes are discussed in terms of the propagation and generation of coastal-trapped waves. Highlights: Diurnal tidal currents are dominant on the Pacific shelf off Hokkaido. Diurnal tidal currents are characterized by 200-km small-scale wavelengths. Diurnal tidal currents are attributed to free baroclinic coastal-trapped waves. Diurnal tidal elevation is controlled mainly by barotropic gravity waves. Diurnal tidal currents undergo considerable seasonal variation.